Pengurusan Penyenggaraan Fasiliti Bangunan Kediaman Flat di Batu Pahat - Adam, Mohd Amin Nasrin; Mohamed, Sulzakimin; Sarpin, Norliana; Mat Radzuan, Indera Syahrul; Khalid, Zailawati (Research in Management of Technology and Business, 2023)
Management is one of the important elements in a construction project. One of the important managements in the construction industry after the completion of a project is the management of facility maintenance. Among the problems that occur is that the maintenance carried out does not meet the rules and standards that have been set. There are also tax-related problems and burdensome maintenance fees. This study focuses on the area in Batu Pahat. The first objective of this study is to identify the management of facility maintenance carried out in flat homes in Johor. While the second objective is to study the level of satisfaction and needs of flat residents in Johor. Data collection and information was made through a survey of 102 respondents. This study has also been successful in achieving its objectives based on the information that has been analyzed and formulated. The Likert method is also used to help to obtain the results of the study. Based on the analysis that has been made, the effectiveness of facility maintenance management is to influence the level of consumer satisfaction with the maintenance of the facility of a building or area. Not only that, this shows that the maintenance management carried out also meets the needs and satisfaction of the residents at the Flat Residence in Batu Pahat. Therefore, all parties must together take care of the facilities provided and always cooperate with those who carry out maintenance work so that the facilities can be maintained in good condition and safe.